Lead Abandonment and Subcutaneous Implantable Cardioverter-Defibrillator (S-ICD) Implantation in a Cohort of Patients With ICD Lead Malfunction - Russo, Vincenzo; Viani, Stefano; Migliore, Federico; Nigro, Gerardo; Biffi, Mauro; Tola, Gianfranco; Bisignani, Giovanni; Dello Russo, Antonio; Sartori, Paolo; Rordorf, Roberto; Ottaviano, Luca; Perego, Giovanni Battista; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background When an implantable-cardioverter defibrillator (ICD) lead becomes nonfunctional, a recommendation currently exists for either lead abandonment or removal. Lead abandonment and subcutaneous ICD (S-ICD) implantation may represent an additional option for patients who do not require pacing. The aim of this study was to investigate the outcomes of a strategy of lead abandonment and S-ICD implantation in the setting of lead malfunction. Methods We analyzed all consecutive patients who underwent S-ICD implantation after abandonment of malfunctioning leads and compared their outcomes with those of patients who underwent extraction and subsequent reimplantation of a single-chamber transvenous ICD (T-ICD). Results Forty-three patients underwent S-ICD implantation after abandonment of malfunctioning leads, while 62 patients underwent extraction and subsequent reimplantation of a new T-ICD. The two groups were comparable. In the extraction group, no major complications occurred during extraction, while the procedure failed and an S-ICD was implanted in 4 patients. During a median follow-up of 21 months, 3 major complications occurred in the S-ICD group and 11 in the T-ICD group (HR 1.07; 95%CI 0.29–3.94; P=0.912). Minor complications were 4 in the S-ICD group and 5 in the T-ICD group (HR 2.13; 95%CI 0.49–9.24; P=0.238). Conclusions In the event of ICD lead malfunction, extraction avoids the potential long-term risks of abandoned leads. Nonetheless the strategy of lead abandonment and S-ICD implantation was feasible and safe, with no significant increase in adverse outcomes, and may represent an option in selected clinical settings. Further studies are needed to fully understand the potential risks of lead abandonment.